Atividade parasiticida in vitro do extrato salino bruto das folhas de prosopis juliflora (sw.) Dc. Sobre a eclosão de ovos de fêmeas de rhipicephalus sanguineus (latreille, 1806) (acari: ixodidae) - Oliveira, Arielle Lima (Universidade Federal Rural do Semi-Árido, 2019)
Due to the number of pathologies transmitted through the species Rhipicephalus sanguineus, there was a necessity of utilizing chemical control methods, causing the selection of resistant ticks. As a result, research and the use of herbal medicines have emerged as a viable alternative for control of these ectoparasites. In this context, the present study aimed to evaluate in vitro the parasiticidal action of Prosopis juliflora crude salt extract on R. sanguineus females, evaluating the mortality and hatching of eggs. To obtain the extract, the leaves of P. juliflora were used, submitted to 10% (w / v) extraction in a 0.15 M NaCl solution under agitation, filtration and centrifugation. The teleogens were collected from domestic dogs, transported and identified, homogenized in groups of eight females, immersed in 10 mL of the extract solution and subjected to two exposure times (10 and 20 minutes), distilled water was used in the negative control and Amitraz for positive control. After immersion, the teleogens were fixed in plates and incubated in B.O.D. As a result, there was an inhibition of the hatched teleogenes hatching, 40% in 10 minutes and 56% in 20 minutes and there was no mortality in the females surveyed. It is concluded that the crude extract of P. juliflora presented ovicidal activity in the tested females, as a viable alternative in biological control.
Keywords: Cão doméstico; Carrapato; Controle biológico; Domestic dog; Tick; Biologic control; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA